Enhancing language and print-concept skills by using interactive storybook reading in kindergarten. (December 2018) - Nevo, Einat; Vaknin-Nusbaum, Vered
The effectiveness of a short interactive storybook-reading intervention programme delivered by a kindergarten teacher to develop language and print-concept skills was examined in 30 Hebrew-speaking kindergarten children exhibiting different levels of emergent literacy skills. Post-intervention, the intervention group showed a clear advantage over a control group on most measures, including vocabulary, morphology, phonological awareness and print concepts. Pre-test motivation to read was predictive of post-test performance in these same language and print-concept skills. The study suggests that a short intervention programme, using stories and embedded activities, can enhance language and print concepts in kindergarten children; and that motivation to read is equally important in the development of their language and literacy abilities.